Universidade corporativa : projeto do capital para a formação dos trabalhadores - Longano, Priscila de Freitas (2007)
This paper has the objective of analyzing the professional formation processes coming from the Corporate University. It discusses the precepts of businessmen toward the formation of workers as well as the criticisms created by them concerning the inefficiency of formal schools in the education of the workforce in relation to the needs of the enterprises. Taking as reference the precepts of the alienation by and through work and the crisis of the monopolistic capitalism that imposes drastic conditions of exploitation at the work place, we discuss the capitalist concepts of human education defending that the capitalist informal education project is ideological and contradictory. Contrary to the making of wiser men and holders of technology, what can be seen is the continuation of precarious and alienated forms of work.